INCREASING THE COMPETITIVENESS OF AN OPEN UNIVERSITY IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Oksana Buinytska; Valeriia Smirnova (Borys Grinchenko Kyiv Metropolitan University, 2024)
Digital transformation and globalization processes require universities to adapt to new challenges and demands of society and integrate the principles of sustainable development into all areas of their activities. Under martial law, the issue of increasing the competitiveness of universities is particularly relevant. Each university seeks to attract the most talented students, teachers, and researchers. One of the tools for assessing the competitiveness of universities is international rankings, including those aimed at measuring the achievements of universities in the field of sustainable development and their contribution to the implementation of the Sustainable Development Goals, which are an indicator of effective management and improvement of the quality of education for its sustainability. The key rankings that rank universities by their contribution to the Sustainable Development Goals are the Times Higher Education Impact Rankings, QS World University Rankings, and UI GreenMetric. Based on the analysis of the methodologies of these rankings, are identified the main criteria and indicators used in each of the rankings that have a significant impact on the competitiveness of the university in the context of sustainable development. The analysis made it possible to outline the guidelines for the university's activities to improve its ranking in the context of sustainable development, and the recommendations of the European Association of Universities prompted and became the basis for the development of the Roadmap (Policy) for Sustainable Development, which consolidates key strategic guidelines aimed at systematic integration of sustainable development principles in the areas of the university's activities: education for sustainable development, research and innovation, social impact, public engagement, partnership and cooperation, image and sustainable reputation, sustainable infrastructure. The Sustainable Development Roadmap (Policy) is aimed at systematically integrating sustainability principles into the educational process, research, and management processes of the university. The goals identified by the areas of activity will serve as indicators for the development of an internal sustainability rating of the university's structural units, which will improve the university's ranking in international sustainability rankings and ensure its competitiveness.